Molecular subtype identification and signature construction based on Golgi apparatus-related genes for better prediction prognosis and immunotherapy response in hepatocellular carcinoma - Sun, Liang; Liu, Zitao; Wu, Zhengyi; Ning, Ke; Hu, Junwen; Chen, Zhendong; Wu, Zhipeng; Yin, Xiangbao (Frontiers in Immunology, 2023)
BACKGROUND: The Golgi apparatus (GA) is the center of protein and lipid synthesis and modification in normal cells and acts as a signal hub involved in the regulation of a variety of cellular processes, the dysfunction of which can lead to the development of a variety of pathological conditions, including tumors. Mutations in Golgi apparatus-related genes (GARGs) are prevalent in most tumors and their mutations can make them pro-tumor metastatic genes. The aim of this study was to analyze the predictive role of GARGs in prognosis and immunotherapeutic outcome in hepatocellular carcinoma. Using the TCGA, GEO and ICGC public databases, inter-tumor molecular heterogeneity in hepatocellular carcinoma identified two major subtypes based on the expression of GARGs, with C1 as the high-risk subtype (low survival) and C2 as the low-risk subtype (high survival). The high-risk subtypes had lower StromalScore, ImmuneScore, ESTIMATEScore and higher TumorPurity, indicating poorer treatment outcome of ICIs. Meanwhile, we constructed a new risk assessment signature for hepatocellular carcinoma based on GARGs, and we found that the high-risk group had a worse prognosis, a higher risk of immune escape and a higher rate of TP53 mutations. Meanwhile, TME analysis showed higher tumor purity TumorPurity and lower ESTIMATEScore, ImmuneScore and StromalScore in the high-risk group. We also found that the high-risk group was more responsive to multiple anti-cancer drugs, which is useful for guiding clinical dosing. In addition, we established a nomogram for clinical application. We used GARGs for the first time in the construction of a prognostic signature for hepatocellular carcinoma to predict clinical prognosis and guide the treatment of HCC patients.